2000
DOI: 10.1182/blood.v96.9.2917
|View full text |Cite
|
Sign up to set email alerts
|

CD40-ligand (CD154) gene therapy for chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) cells can be made to express recombinant CD40-ligand (CD154) by transduction with a replication-defective adenovirus vector (Ad-CD154). Ad-CD154–transduced and bystander leukemia cells become highly effective antigen-presenting cells that can induce CLL-specific autologous cytotoxic T lymphocytes in vitro. This study investigated the immunologic and clinical responses to infusion of autologous Ad-CD154-CLL cells in patients with CLL. After a one-time bolus infusion of autolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Finally, the neoplastic cells were inhibited in their growth kinetics. These results are interesting in view of the recently presented results from a phase I trial on CD40L gene transfer in CLL (5, 130).…”
Section: Immunological Approachesmentioning
confidence: 82%
“…Finally, the neoplastic cells were inhibited in their growth kinetics. These results are interesting in view of the recently presented results from a phase I trial on CD40L gene transfer in CLL (5, 130).…”
Section: Immunological Approachesmentioning
confidence: 82%
“…Kipps described a gene therapy approach where 3 × 10 8 –3 × 10 9 CD40L‐transfected autologous leukemia cells were infused into CLL patients. These cells induced the expression of immune accessory signals on noninfected bystander CLL cells, leading to T‐cell proliferation, cytokine secretion, expansion of leukemia specific T cells, reduction of CLL cell counts and lymph node size 33. It is conceivable that CIK cells, in addition to their immediate cytotoxicity, may have a similar effect in CLL patients, allowing activation of leukemia cells in vivo without the need for gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treated patients had high plasma levels of the Th1‐type cytokines IL‐12 and IFN‐γ after infusion. T‐cell responses against autologous CLL cells, as evidenced by increased IFN‐γ secretion as well as T‐cell proliferation in an autologous MLR, were observed even at 6 months after treatment, indicating the development of memory antileukemia immune responses 22. Long‐term follow‐up studies showed that although the number of blood leukemic cells increased after a one‐time injection of Ad‐CD40L‐transduced cells, repeated injections resulted in a stabilized and reduced leukemia cell counts and disease stabilization.…”
Section: Cd154 Gene Therapy Trial For Cllmentioning
confidence: 99%
“…1). 22 We investigated the immunological and clinical responses to infusion of Ad‐CD154‐CLL cells into eleven patients with progressive, intermediate, or high‐risk CLL. Patients received infusion of transduced CLL cells on average 44+/− 23 days after leukapheresis.…”
Section: Cd154 Gene Therapy Trial For Cllmentioning
confidence: 99%